أثر الرافعة المالية على الربحية دراسة تطبيقية على الشركات غير المالية المدرجة في سوق دمشق للأوراق المالية - كنعان, علي; ساعود, علي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تهدف الدراسة إلى الكشف عن أثر الرافعة المالية على ربحية الشركات غير المالية المدرجة في سوق دمشق للأوراق المالية ومدى امكانية استخدام الديون في زيادة الربحية، ولتحقيق اهداف الدراسة تم جمع البيانات اللازمة لمتغيرات الدراسة ، وهي المتغير المستقل الممثل بالرافعة المالية وذلك عبر النسب التالية:( نسبة تمويل اصول الشركة ممثلة بنسبة الاقتراض ونسبة الرفع المالي ممثلة بإجمالي الاصول الى حقوق الملكية وحجم الديون طويلة الاجل المستخدمة مقارنة بحقوق الملكية معبرا عنها بنسبة الديون )، أما المتغير التابع الربحية فعّبر عنه( بمعدل العائد على الاصول ). وذلك بالاعتماد على القوائم المالية المدققة للشركات غير المالية المدرجة في سوق دمشق للأوراق المالية خلال الفترة من 2008 حتى 2016حيث تم استخدام البرنامج الاحصائي SPSS لاختبار العينة وذلك باستخدام الانحدار الخطي ، وخلصت الدراسة بعد اجراء عملية التحليل لبيانات الدراسة الى أن للرافعة المالية أثر ذو دلالة معنوية على الربحية في الشركات غير المالية المدرجة في سوق دمشق للأوراق المالية، أوصت الدراسة زيادة القروض والتسهيلات الممنوحة للشركات لما لذلك من أثر ايجابي على ربحيتها و إلى توسيع إطار الأبحاث المستقبلية من حيث الحدود الزمانية و المكانية وحجم العينة, وعدم الاقتصار على الشركات الصناعية والخدمية فحسب، بل وأن تشتمل على القطاعات الأخرى المدرجة في سوق دمشق للأوراق المالية ومقارنة نتائجها مع الاسواق الأخرى في المنطقة . The study aims to reveal the influence of the financial leverage on the profitability of non-financial companies listed on the Damascus Financial Market(DFM) and the extent of the possibility of using the debt to increase profitability. To achieve the objectives of the study, the necessary data were collected for the variables of the study which is independent variable financial expressed as: Financing of the assets of the company represented by the rate of borrowing and the leverage ratio represented by total assets to equity and the long-term debt used in relation to equity as expressed by the debt ratio. The dependent variable profitability is expressed as the return on assets. Based on the audited financial statements of non-financial companies listed on, the Damascus Financial market, during the period from 2008 to 2016. The statistical program SPSS was used to test the sample using linear regression. The study concluded after the analysis of the study data that the financial leverage has a significant impact on profitability in the non-financial companies listed on the DFM, the study recommended increasing the loans and facilities granted to companies because of the positive impact on their profitability and to expand the framework of future research in terms of temporal and spatial boundaries and sample size , And not only the industrial and service companies, but also include other sectors listed on the Damascus Stock Exchange and compare their results with other markets in the region.